Bronchial challenge in perennial allergic rhinitis patients without asthma – A clinico spirometric correlation - Dr. PRAKASH M; Dr. HARI P M; Dr. PAVITHRA SAIKUMAR (International Journal of Pharma and Bio Sciences, 2017)
The aim of the study is to study and categorize the drop of FEV1 values in patients with Perennial Allergic Rhinitis patients without asthma after a bronchial challenge and have a clinic spirometric correlation. Also to estimate and analyze FEV1 values in Perennial allergic rhinitis patients and to find out changes in FEV1 values in Perennial allergic rhinitis after administrating nebulized distilled water- bronchial hyper responsiveness test. Consenting patients were given a standard questionnaire and perennial allergic rhinitis patients were diagnosed based on the available criteria. Their base level FEV1 were estimated and bronchial challenge with distilled water nebulization was done and the change in the FEV1 recorded. It was found that 56 percent of patients with perennial allergic rhinitis had a significant reduction ie severe reduction [>20%] of FEV1 values and only 5 percent had no change in their FEV1 values. This confirms the very concept of allergic rhinitis as a risk factor for development of bronchial asthma and that of the unified airway. So adequate control measures of allergic rhinitis is essential to ensure that the patient does not suffer a lower respiratory illness secondary to allergic rhinitis. All these people with severe reduction will be the ones who develop bronchial asthma in the future. So they have to be monitored closely with serial spirometric tests so that we can diagnose likely asthmatics and institute appropriate measures.